PROFILING PESERTA DIDIK SEBAGAI FONDASI PEMBELAJARAN BERDIFERENSIASI DI SEKOLAH DASAR - Ekarani, Dewi; Deby Nuraisyah; Gina Faojina; Ilah Nurlaelah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Student profiling is a systematic process of identifying and mapping individual student characteristics including abilities, interests, learning styles, learning readiness, and socio-cultural backgrounds. This process is essential for teachers in designing effective student-centered learning, particularly in the context of differentiated instruction. This article aims to conceptually examine the relationship between student profiling and the implementation of differentiated learning in elementary schools. The method used is a literature review by analyzing various relevant scientific sources. The results show that student profiling plays a strategic role as the foundation of differentiated learning through mapping aspects of student characteristics such as academic ability, learning style, learning readiness, interests, socio-emotional development, and special needs. Profiling data obtained through diagnostic assessments helps teachers design content, process, and product differentiation appropriately. Without adequate profiling, teachers risk designing learning that does not meet student needs, resulting in low motivation, learning gaps, and suboptimal development of student potential.